Data Driven Decision-Making for Complex Production Systems - Yang, Zaoli; Li, Yuchen; Kucukkoc, Ibrahim (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The complexity of production processes is on the rise due to evolving technology and changing lifestyles. This complexity can stem from factors within the production system or be influenced by characteristics or events external to the system. This reprint aims to conduct rigorous research focused on the application of data-driven decision-making algorithms to address diverse challenges within complex production systems.